The Dynamics of Good Governance and the Legislative Function of the Regional People's Representative Council (DPRD) - Ayu Sita Dewi Wijayanti; Ni Wayan Widhiastini (Bulletin of Community Engagement, 2026)
This study examines the dynamics of good governance implementation in the legislative function of the Badung Regency Regional People's Representative Council (DPRD) within the regional regulation (Perda) formation process. Employing a qualitative descriptive-interpretative approach with triangulation of in-depth interviews, field observations, and document analysis of the 2025 Propemperda program, findings reveal DPRD Badung's high productivity, converting 10 Draft Regional Regulations (Raperda) into 9 Perda (90% success rate), surpassing the national average. The organizational structure 45 members dominated by PDI-P (67%) facilitates efficient musyawarah through key bodies like Bapemperda (11 members) and four commissions (41 members), supported by 37 mandatory socialization events involving 11,100+ citizens. Good governance principles score 8.2/10, with strengths in participation, transparency, and efficiency, but challenges in legal drafting capacity (1.8% budget allocation) and factional dominance persist. A novel "Badung Legislative Collaborative Governance Model" emerges, integrating political dynamics, public participation, and vertical harmonization with central regulations. Recommendations include boosting academic paper funding to 5% of the legislative budget and digital aspiration platforms for enhanced inclusivity.